Comparative Effectiveness of Low-Carbon and Balanced Diet In Type 2 Diabetes Mellitus - Angelina Gosudarskaia (International Journal of Medical Sciences And Clinical Research, 2025)
This article presents a review of the comparative effectiveness of low-carbohydrate and balanced carbohydrate diets in type 2 diabetes. The results of randomized controlled trials and meta-analyses published between 2014 and 2025 were analyzed, assessing the impact of diets on glycated hemoglobin levels, body weight, and lipid profiles. Both diets were found to reduce HbA1c and body weight, with minimal differences between them.